The Nutritional Education Effect Of Healthy Snacks With Quartet Card Media Toward Elementary School Students’ Nutritional Knowledge - yuli laraeni; I Nyoman Adiyasa; Lalu Khairul Abdi; Risma Widianti (Poltekkes Kemenkes Mataram, 2023)
Background: The students at school age are categorized into a risky period toward health problems. The health condition of students at elementary school affects the student's achievements. The education on nutrition given to them effectively shifts toward healthy eating behavior. Some efforts were made to provide nutrition education for elementary school-aged children through attractive media to support accessible materials conveyed. One engaging medium that is